Azospirillum thermophilum sp. nov., isolated from a hot spring. Issue 1 (3rd February 2020) - Zhao, Zhuo-li; Ming, Hong; Ding, Chen-Long; Ji, Wei-Li; Cheng, Li-Jiao; Niu, Ming-ming; Zhang, Yan-min; Zhang, Ling-Yu; Meng, Xiao-Lin; Nie, Guo-Xing
Abstract : A novel Gram-staining negative, aerobic, motile by flagellum, rod-shaped bacterium, designated CFH 70021 T was isolated from a hot spring soil sample collected from Tengchong, Yunnan province, PR China. Growth of CFH 70021 T occurred at 15–50 °C (optimum 50 °C), pH 5.0–7.0 (optimum pH 7.0) and with 0–3.0 % (w/v) NaCl (optimum 0 %, w/v). The genome of CFH 70021 T consisted of four complete circular chromosomes and five plasmids, the genomic DNA G+C content was 69.3 mol%. Comparison of the 16S rRNA gene sequences indicated that CFH 70021 T represented a member of the genus Azospirillum and showed close relationship with the type strains of Azospirillum agricola CC-HIH038 T (97.8 %), Azospirillum rugosum IMMIB AFH-6 T (97.6 %), Azospirillum doebereinerae GSF71 T (97.6 %), Azospirillum thiophilum DSM 21654 T (97.4 %) and Azospirillum picis IMMIB TAR-3 T (97.2 %). The polar lipids of CFH 70021 T contained diphosphatidylglycerol, phosphatidylmehtylethanolamine, phosphatidylglycerol, phosphatidylcholine, two aminolipids and an unidentified phospholipid. The predominant cellular fatty acids (>10 %) included C19:0 cyclo ω 8c (11.4 %), C16 : 0 (27.6 %) and summed feature 8 (C18:1 ω7 c /C18:1 ω6 c, 40.9 %). The major isoprenoid quinone was Q-10. On the basis of the low ANIb result (<78 %) and different phenotypic and chemotaxonomic characters, we conclude that strain CFH 70021 T represents a novel member of the genus Azospirillum, for which the name Azospirillum thermophilum sp. nov. is proposed. The type strain is CFH 70021 T (=KCTC 62259 T = CCTCC AB2018121 T ).